Work sampling assessment of ASHA workers in urban and rural field practice areas of a tertiary teaching hospital, Bangalore: A mixed method study - Shruthi M. Shetty; Priyanka D. Shivarama; Renuka Venkatesh; M. Ashwini (Journal of Family Medicine and Primary Care, 2025)
Introduction: To meet the health demands in urban areas, the cadre of ASHA was created to work as a Community Health Worker (CHW) based in the community, delivering services under various programmes. It is necessary to assess the work profile of the ASHA workers to understand the challenges faced by them and to motivate them to perform their responsibilities effectively and efficiently. Objectives: To assess the performance of services delivered by ASHA workers in the Health Care Centres. Methodology: The study was conducted in Urban and Rural Health Centre of a Medical College, Bengaluru. In-depth interviews were conducted on 26 ASHA workers to collect information about factors influencing their performance, training, and financial aspects. Data was entered into Microsoft Excel and analysed with SPSS version 22. Quantitative data was expressed using descriptive statistics. For analysis of in-depth interviews, themes were identified and findings were reported by using Consolidated Criteria for Reporting Qualitative Research. Results: The mean age of the women was 36.5±5.4 years all were married and of Hindu religion. The majority of the ASHA workers have completed 10th Standard, 16 (61.53%). 30.76% of the ASHA workers had 13 years of experience, though they lacked knowledge and had poor performance in the areas of child health and tuberculosis. Conclusion: The need of the hour is to reinforce the ASHA workers with knowledge and financial incentives on a regular basis for the betterment of the society.